A chain mediation model of parent child relationship and academic burnout of adolescents - Jiangnan Sun; Hang Guo; Wenxin Jiang; Xiuqing Chen; Fengyao Wu; Zisen Zhuang; Zhangya Lin (Scientific Reports)
Abstract This paper studied the relationship and mechanisms of parent–child relationship, interpersonal relationship on campus, academic self-efficacy and academic burnout among adolescents. A study of 913 Chinese junior high school students from Fujian province (47.20% males, mean age = 13.99 years, SD = 0.81) was conducted using the Junior Middle School Students’ Learning Weariness Scale, the Chinese version of parent–child affinity scale, the Loso Wellbeing Questionnaire, and the Academic Self-efficacy Questionnaire. (1) Academic burnout was negatively and significantly correlated with parent–child relationship (r = − 0.13, p < 0.01), interpersonal relationship on campus (r = − 0.11, p < 0.01), and academic self-efficacy (r = − 0.13, p < 0.01). Parent–child relationship was positively and significantly correlated with interpersonal relationship on campus (r = 0.23, p < 0.01) and academic self-efficacy (r = 0.38, p < 0.01). Interpersonal relationship and academic self-efficacy were positively and significantly correlated (r = 0.29, p < 0.01). (2) Parent–child relationship can significantly and negatively predicte academic burnout (β = − 0.082, p < 0.05). (3) Parent–child relationship affected academic burnout of adolescents via three significant indirect effects: the single mediating effect of interpersonal relationship on campus (effect = − 0.011) and academic self-efficacy (effect = − 0.019), and the chain mediating effect of interpersonal relationship on campus and academic self-efficacy (effect = − 0.003). Stronger parent–child relationship predicts lower levels of academic burnout. Moreover, parent–child relationship can indirectly affect academic burnout not only through the single mediating effect of interpersonal relationship on campus and academic self-efficacy but also through the chain mediating effect of interpersonal relationship on campus and academic self-efficacy.